Study on the Influence of Weather Factors on Construction Delays of Retaining Walls in Market Projects - Junita Eka Susanti (Universitas Islam Raden Rahmat, Malang, 2025)
Weather is an external factor that significantly influences the implementation of construction projects, especially in open environments. This research aims to evaluate the impact of weather, particularly rainfall, on delays in retaining wall construction projects in market areas. The study employs statistical analysis of historical weather data, an assessment of work progress realization, and interviews with project implementers. The analysis reveals that rainfall, both drizzle and heavy rain, affects work productivity differently. During the project timeline, rain occurred for 17 days in October (48 hours), 21 days in November (74 hours), and 7 days in December (20 hours). In the first month, progress exceeded the planned schedule with a positive deviation of 4.25%. However, in the second month, adverse weather conditions and other technical factors contributed to a negative deviation of 6.88%. Despite this setback, work progress recovered in the third month, ultimately reaching the targeted 100% completion. Regression analysis confirms that heavy rain significantly hampers construction activities more than drizzle. Significant tasks, such as the construction of retaining walls, come to a complete halt during heavy rain, whereas drizzle still allows work to proceed, albeit with reduced productivity. These findings underscore the necessity of integrating weather risk assessments into project planning to develop more resilient scheduling strategies and minimize potential delays.